2000
DOI: 10.1159/000007764
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of HGF and Its Receptor in Human Colorectal Cancer

Abstract: Background: Hepatocyte growth factor (HGF) stimulates proliferation, migration and morphogenesis of epithelial cells by specific binding to its receptor c-met. Overexpression of HGF or c-met has been reported for human gastric or pancreatic cancer. In colorectal cancer overexpression of c-met but not HGF has been shown. However, elevated HGF serum levels have been detected in colorectal cancer patients. Therefore, the present study was performed to investigate expression patterns of both c-met and HGF in color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 29 publications
2
51
1
Order By: Relevance
“…When interpreting these data, several aspects regarding HGF-MET interactions are of interest. Whereas MET was expressed in cells of epithelial origin, HGF expression was mostly confined to mesenchymal cells suggesting paracrine effects on the tumor cells (16), as confirmed by our results. On the other hand, HGF bioactivity may be controlled by tumor-cell derived factors such as HGF activator (HGFA) and its inhibitor HGFA inhibitor type 1 (HAI-1), which are both detected in colorectal mucosa as well as neoplasms (45).…”
Section: ------------------------------------------------------------supporting
confidence: 89%
See 1 more Smart Citation
“…When interpreting these data, several aspects regarding HGF-MET interactions are of interest. Whereas MET was expressed in cells of epithelial origin, HGF expression was mostly confined to mesenchymal cells suggesting paracrine effects on the tumor cells (16), as confirmed by our results. On the other hand, HGF bioactivity may be controlled by tumor-cell derived factors such as HGF activator (HGFA) and its inhibitor HGFA inhibitor type 1 (HAI-1), which are both detected in colorectal mucosa as well as neoplasms (45).…”
Section: ------------------------------------------------------------supporting
confidence: 89%
“…HGF/SF levels vary in many pathologic and physiologic processes (15) and are especially important in injury, differentiation and growth. Otte et al described the functional expression of HGF and MET in colorectal cancers and suggested a paracrine mechanism of growth enhancement (16). The multiple features and properties of MET and HGF have been described in great detail in the review by Birchmeier et al (17).…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Many studies have reported overexpression of cMet or an HGF receptor by colorectal cancer. [30][31][32][33] Increased cell movement induced by HGF requires activation of Rho protein, and Rac and Rho are involved in cell membrane ruffling during the cell movement caused by HGF. 34 HGF controls the WASP family protein N-WASP, and is related to cell movement and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Even though c-MET mRNA is present at very small amounts in normal human exocrine pancreas, it is upregulated in a majority of PDAC. Interestingly overexpression of c-MET has been observed in regenerative tissue affected by acute pancreatitis (Otte et al 2000), and has been linked to early events in PDAC carcinogenesis. HGF is a primary ligand of c-MET.…”
Section: Complex De-regulatory Signaling Mechanisms In Pdacmentioning
confidence: 99%